Cloud computing security risks with authorization access for secure Multi-Tenancy based on AAAS protocol - Abd S.K.; Salih R.T.; Al-Haddad S.A.R.; Hashim F.; Abdullah A.B.H.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Access control; Cloud computing; Distributed database systems; Open systems; Web services; Authorization systems; Cloud computing securities; Cloud infrastructures; Cooperation agreement; Multi tenancies; Multi-tenancy architectures; Open system architecture; Security risks; Network architecture